2021
DOI: 10.3390/buildings11030109
|View full text |Cite
|
Sign up to set email alerts
|

An Overarching Review on Delay Analyses in Construction Projects

Abstract: Numerous studies have been conducted by researchers on the delay analysis topic, which is one of the primary areas of scientific study due to the effects of delays on time and cost in construction projects. Following fruitful contributions made by the researchers, it is believed to be extremely important to summarize the existing studies in terms of being a road map for future studies and practitioners. In this context, not only does this study aim to detect the most significant authors, sources, organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…The color, shape, and size of the nodes, namely the intersection points in the network, are changeable through their attributes [96]. VOSviewer is a visual analysis tool of literature developed by Leiden University in the Netherlands, by which the visualization of the knowledge unit is implemented based on VOS clustering technology [97][98][99]. HistCite is a free system for the link analysis of scientific literature and visualization, developed by Eugene Garfield et al in 2001 [100], through which the citation data of SCI, SSCI, and SA & HCI databases of ISI can be quantitatively analyzed to generate a matrix and real-time dynamic chronology of literature, authors, and journals.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The color, shape, and size of the nodes, namely the intersection points in the network, are changeable through their attributes [96]. VOSviewer is a visual analysis tool of literature developed by Leiden University in the Netherlands, by which the visualization of the knowledge unit is implemented based on VOS clustering technology [97][98][99]. HistCite is a free system for the link analysis of scientific literature and visualization, developed by Eugene Garfield et al in 2001 [100], through which the citation data of SCI, SSCI, and SA & HCI databases of ISI can be quantitatively analyzed to generate a matrix and real-time dynamic chronology of literature, authors, and journals.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…This suggests the importance that has historically been attached to research on construction project delays in KSA [15]. A more recent review of the historical causes of delay examined 168 studies done between 1982 and 2021 and found that six major themes emerged in construction delay research: the framework for analyzing delays, a dynamic building information modelling (BIM) 4D-BIM based analysis of delays, new models for delay analysis, the selection of methods for delay analysis, critical chain management, and blockchain/smart contracts in delay management [16].…”
Section: Literature Review 21 Construction Delays In Global Contextmentioning
confidence: 99%
“…There are many classification methods of construction cost, which are generally classified according to different standards and different application scopes. At present, the main classification methods are the cost valuation quota method and the project completion degree method [ 11 ].…”
Section: Introduction Of Construction Project Costmentioning
confidence: 99%